Valuing ecosystem diversity in South East Queensland: A life satisfaction approach - Ambrey, C; Fleming, C. M. (Asia Pacific Centre for Sustainable Enterprise, 2012)
The purpose of this paper is to use the life satisfaction approach to value ecosystem diversity in the South East Queensland bioregion. A respondent’s self-reported life satisfaction is a function of a number of socio-economic and demographic characteristics (including income) and is hypothesised to be a product of the degree of ecosystem diversity in an individual's local area. Results indicate that high levels of ecosystem diversity, ceteris paribus, increase self-reported life satisfaction. Specifically, we find that a one-unit improvement in ecosystem diversity is equivalent (in life satisfaction terms) to an increase in household income per annum of approximately AUD $11,000.
Asia Pacific Work In Progress research Paper series
Keywords: Location -- QLD; Satisfaction -- Life; Housing, communities and neighbourhoods; Location; Satisfaction; QLD; Life; Housing, community and neighbourhoods